دلالة المصطلح اللًّغوي عند الإمام الغزالي ت: 505هـ في " المستصفى من علم الأصول " - طالب أميمة علي جمعة (Al-Qurtas, 2025)
دلالة المصطلح اللًّغوي عند الإمام الغزالي ت: 505هـ في " المستصفى من علم الأصول "